Aerodynamic Performance of the NACA 0012 Airfoil: Lift and Drag Characteristic Across a Range of Angles of Attack - Septiawan, Dedy; Yuliaji, Dwi; Waluyo, Roy (Master Program in Mechanical Engineering, Gunadarma University, 2026)
The wing is one of the most critical components in an aircraft structure, as it directly contributes to the generation of lift, which enables flight. Without wings, an aircraft would be unable to produce lift or counter aerodynamic drag effectively. This study aims to analyze the lift and drag forces acting on a NACA 0012 airfoil under varying angles of attack and flow velocities. Two approaches were employed: numerical simulations using ANSYS Fluent to investigate airflow patterns and pressure distribution on the upper and lower surfaces of the airfoil, and experimental testing in a wind tunnel to validate and complement the findings. The experiments considered angles of attack of 0°, 3°, 6°, and 9°, with freestream velocities of 1 m/s and 3 m/s. The quantitative data collected include lift coefficient (CL), drag coefficient (CD), the relationships between CL–α, CD–α, and CL–CD, as well as pressure and velocity distributions from the CFD simulations. Both computational and experimental results indicate that increasing the angle of attack produces a significant change in the lift and drag characteristics of the airfoil. In conclusion, variations in the angle of attack have a substantial impact on the aerodynamic flow behavior around the airfoil and on the magnitude of the resulting lift and drag forces.